ANALISIS FORMAL DAN INFORMAL FISIK PERMUKIMAN TEPIAN SUNGAI KAHAYAN KOTA PALANGKA RAYA - Noor Hamidah; R Rijanta; Bakti Setiawan; Muh. Aris Marfai (Diponegoro University, 2017)
Most of the settlement in Indonesia are located along big river. Kampung Pahandut is one of riverside settlement, thatis to observe in this research. Kampung Pahandut is a first settlement before growth to urban area. Kampung Pahandut is a source of life and ease to access of transport between regions. Research of settlement integration is one of alternative to solve of settlement problem in Indonesia. Settlement consist of: (1) nature; (2) shell/house; (3) network; (4) man; and (5) community. This research only focus on analysis of physical integration (1) nature; (2) shell/house; and (3) network especially natural settlement with the unique of riverside architecture. The objective of this research was to explore the pattern of settlements as an adaptation to the physical environment riverside area and to analyses the physical, economic and social apart of integration of urban riverside settlement. Research method used a combination (mix-used method) based on field observation and quesioner with 50 sample representated on one villages of Pahandut. The results showed there are threevariables that affect to riverside settlement, namely: (1) nature; (2) settlement; and (3) network.. The three variable of the settlement pattern support settlements in those areas riverside towards sustainable development through to riverside area.